Study of Wind Loads and Wind Speed Amplifications on High-Rise Building with Opening by Numerical Simulation and Wind Tunnel Test - Fu-Bin Chen; Xiao-Lu Wang; Yun Zhao; Yuan-Bo Li; Qiu-Sheng Li; Ping Xiang; Yi Li (Advances in Civil Engineering)
High-rise buildings are very sensitive to wind excitations, and wind-induced responses have always been the key factors for structural design. Facade openings have often been used as aerodynamic measures for wind-resistant design of high-rise buildings to meet the requirement of structural safety and comfort. Obvious wind speed amplifications can also be observed inside the openings. Therefore, implementing wind turbines in the openings is of great importance for the utilization of abundant wind energy resources in high-rise buildings and the development of green buildings. Based on numerical simulation and wind tunnel testing, the wind loads and wind speed amplifications on high-rise buildings with openings are investigated in detail. The three-dimensional numerical simulation for wind effects on high-rise building with openings was firstly carried out on FLUENT 15.0 platform by SST k−ε model. The mean wind pressure coefficients and the wind flow characteristics were obtained. The wind speed amplifications at the opening were analyzed, and the distribution law of wind speed in the openings is presented. Meanwhile, a series of wind tunnel tests were conducted to assess the mean and fluctuating wind pressure coefficients in high-rise building models with various opening rates. The variation of wind pressure distribution at typical measuring layers with wind direction was analyzed. Finally, the wind speed amplifications in the openings were studied and verified by the numerical simulation results.